Splicing Enhancers at Intron-Exon Borders Participate in Acceptor Splice Sites Recognition - Kováčová, Tatiana; Souček, Přemysl; Hujová, Pavla; Freiberger, Tomáš; Grodecká, Lucie (International journal of molecular sciences, 2020)
Acceptor splice site recognition (3' splice site: 3'ss) is a fundamental step in precursor messenger RNA (pre-mRNA) splicing. Generally, the U2 small nuclear ribonucleoprotein (snRNP) auxiliary factor (U2AF) heterodimer recognizes the 3'ss, of which U2AF35 has a dual function: (i) It binds to the intron-exon border of some 3'ss and (ii) mediates enhancer-binding splicing activators' interactions with the spliceosome. Alternative mechanisms for 3'ss recognition have been suggested, yet they are still not thoroughly understood. Here, we analyzed 3'ss recognition where the intron-exon border is bound by a ubiquitous splicing regulator SRSF1. Using the minigene analysis of two model exons and their mutants, BRCA2 exon 12 and VARS2 exon 17, we showed that the exon inclusion correlated much better with the predicted SRSF1 affinity than 3'ss quality, which were assessed using the Catalog of Inferred Sequence Binding Preferences of RNA binding proteins (CISBP-RNA) database and maximum entropy algorithm (MaxEnt) predictor and the U2AF35 consensus matrix, respectively. RNA affinity purification proved SRSF1 binding to the model 3'ss. On the other hand, knockdown experiments revealed that U2AF35 also plays a role in these exons' inclusion. Most probably, both factors stochastically bind the 3'ss, supporting exon recognition, more apparently in VARS2 exon 17. Identifying splicing activators as 3'ss recognition factors is crucial for both a basic understanding of splicing regulation and human genetic diagnostics when assessing variants' effects on splicing.
Keywords: sestřih RNA; lidé; Base Sequence; RNA Splicing Factors; HeLa Cells; Regulatory Sequences, Nucleic Acid; místa sestřihu RNA; RNA Splice Sites; RNA-Binding Proteins; regulační oblasti nukleových kyselin; Serine-Arginine Splicing Factors; spliceozomy; Humans; Introns; RNA Splicing; Alternative Splicing; serin-arginin sestřihové faktory; Splicing Factor U2AF; sestřihový faktor U2AF; alternativní sestřih; HeLa buňky; exony; proteiny vázající RNA; Spliceosomes; sestřihové faktory; introny; Exons; sekvence nukleotidů